Evaluation of slope stability in gullies from Huasca de Ocampo, Hidalgo, Mexico. - Hernández Sánchez, Jazmin Maria de los Dolores; Fernández Reynoso, Demetrio S.; Martínez Menez, Mario R.; Figueroa Sandoval, Benjamín; Rubio Granados, Erasmo; García Rodríguez, José Luis (REVISTA TERRA LATINOAMERICANA, 2019)
In Santo Domingo, Huasca de Ocampo, Hidalgo, changes in the use of soil, the topographic and geomorphological conditions and the increase of runoffs, promote the formation of gullies in agricultural areas, causing the loss of soil fertility and a reduction of agricultural land. The objective of our research was to identify the main topographic features and physical/mechanical properties of the soil that cause a sidewall retreat of gullies (AV); determination was performed through principal component analysis (PCA) and multiple linear regression (MLR). The AV varied from 0.04 to 0.17 m yr‑1 with a mean value of 0.092 m yr-1. The most important variables in the PCA were: height, slope, orientation, vertical and horizontal curvature, transversal slope, ridge thickness, bulk density (0 to 5 and 5 to 10 cm), penetration resistance (2.5, 5 and 10 cm), hydraulic conductivity, shrinkage index, plasticity index, 0.25, 0.15 and 0.075 mm particles, cohesion and soil erodibility factor. The best linear regression explanatory model presented a f it value of 84.02% using four variables (particles of 0.15 and 0.075 mm, slope and ridge thickness). The AV is influenced by the presence of silt and clay in the regolith and soil surface (ridge), which are vulnerable to wetting and drying processes that boost the formation of cracks and disaggregation of the components of ridge and slope, reducing the soil’s resistance to erosion and causing headward erosion and instability in the gully slopes.